2021
DOI: 10.1007/978-3-030-67498-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Emigration, Friends, and Social Integration: The Determinants and Development of Friendship Network Size After Arrival

Abstract: Friendships can be interpreted as voluntary relationships between individuals and characterised as relatively amorphous bond. Since migration usually diversifies people’s social bonds, it can be suggested that in this context friendships have to be reconfigured. Even though friendships are important for societal integration and related to individual well-being, migration research has treated friendships as a side issue. This chapter aims to narrow this gap by answering three questions: Are there significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A lack of social integration, for example, may be associated with decreased health-related quality of life, functional impairment, and severity of depression symptoms, anxiety, and PTSD (37). Similarly, while the beneficial impact of inter-ethnic friendships on the integration and well-being of migrant youths (38,39) and adults (40) has been supported in previous research, the role of friendships in migration research has been largely treated as a side issue (41). Research conducted in Germany has suggested that social capital may facilitate integration of Syrian refugees into the labor market, and that different types of social capital may affect the outcome of the integration process (although the presence of social capital does not invariably lead to the successful utilization of that capital) (42).…”
Section: Introductionmentioning
confidence: 96%
“…A lack of social integration, for example, may be associated with decreased health-related quality of life, functional impairment, and severity of depression symptoms, anxiety, and PTSD (37). Similarly, while the beneficial impact of inter-ethnic friendships on the integration and well-being of migrant youths (38,39) and adults (40) has been supported in previous research, the role of friendships in migration research has been largely treated as a side issue (41). Research conducted in Germany has suggested that social capital may facilitate integration of Syrian refugees into the labor market, and that different types of social capital may affect the outcome of the integration process (although the presence of social capital does not invariably lead to the successful utilization of that capital) (42).…”
Section: Introductionmentioning
confidence: 96%